Intersections Between Violence and Health Promotion Among Indigenous Women Living in Canada - Williams, Julie (Université d'Ottawa / University of Ottawa, 2019)
Violence against Indigenous women is a major public health concern worldwide and Canada is no exception. Multiple forms of violence inform the broader context of violence against Indigenous women. Nurses are likely to encounter Indigenous women in a variety of settings, but evidence suggests that nurses may lack understandings of violence. This thesis explored the following question: How does extant qualitative research conducted in Canada, contribute to understanding the health and wellbeing of First Nations, Métis and Inuit (Indigenous) women who have experienced violence? During the development of this thesis, significant gaps were highlighted including underrepresentation of Inuit women in the literature, limited focus on health promotion, and lack of methodological approaches to systematic reviews that were participatory and inclusive of the community. Therefore, a secondary aim of this thesis was to privilege perspectives of Inuit women and their communities, by developing a study protocol for a collaborative and community centered approach to reviewing and assessing the extant literature. A configurative and inductive approach based on thematic synthesis was used to systematically search, retrieve, analyze and synthesize extant literature. Post-colonial feminist theory and intersectionality were used as theoretical lenses to emphasize intersections between multiple forms of violence and locate the problem within the broader context of colonization and oppression. Sixteen studies were included in this review, fifteen qualitative and one mixed methods study. Four themes with subthemes emerged based on analysis and synthesis of findings in the included studies: 1) ruptured connections between family and home, 2) that emptiness… my spirit being removed, 3) seeking help and feeling unheard, and 4) a core no one can touch. These themes represent interconnected pathways that influenced health among Indigenous women, and have implications for healthy public policy, clinical practice, and nursing education.